Solution to Sea Cargo Mix (SCM) Problem Using Cohort Intelligence Algorithm - Krishnasamy, Ganesh; Kulkarni, Anand Jayant; Abraham, Ajith (Cohort Intelligence: A Socio-inspired Optimization Method, 2017)
The methodology of Cohort Intelligence (CI) (Kulkarni et al. in European Journal of Operational Research, 2015; Bookbinder and Elhedhi in Transportation Research Part C, 21:17–30, 2012; Wong et al. in European Journal of Operational Research 193:86–97, 2009; Deb in Computer Methods in Applied Mechanics in Engineering, 186(2–4):311–338, 2000, [1–4]) has been applied successfully applied solving combinatorial problems such as Knapsack problem, Traveling Salesman Problem and the new variant of the assignment problem (also referred to as Cyclic Bottleneck Problem (CBAP)).